1982
DOI: 10.1111/j.1600-0722.1982.tb00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of and currents between dental metallic restorations

Abstract: Potentials of and currents between dental metallic restorations. Scand. J. Dent. Res. 1982: 90: 404-408. Abstract -115 persons were studied from a body of patients referred to the Faculty of Odontology, University of Umea, for investigation regariding any occurrence of oral galvanism. Potential and polarization of metallic restoradons .and dentures were recorded using a method .and equipment previously described. Data regarding distribution of potential ranges with respect to number of patients and type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
2

Year Published

1984
1984
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…It is interesting to note that the breakdown potentials of the present alloys were all above 1100 mV (SCE). From their in vivo study of 243 restorations from 115 people, Bergman, Ginstrup & Nilsson (1982) have found that the corrosion potentials in the oral enviroment ranged from -550 to -1-400 mV (vs. Ag/AgCI), which were equivalent to approximately -500 to -h450mV (SCE). Since the measured breakdown potentials of the present Ti-Ni alloys were higher than the highest corrosion potential found in the oral environment by as large as 700 mV, it seems that a breakdown of these alloys is very unlikely to occur in the oral environment.…”
Section: Materials and Methods 'mentioning
confidence: 99%
“…It is interesting to note that the breakdown potentials of the present alloys were all above 1100 mV (SCE). From their in vivo study of 243 restorations from 115 people, Bergman, Ginstrup & Nilsson (1982) have found that the corrosion potentials in the oral enviroment ranged from -550 to -1-400 mV (vs. Ag/AgCI), which were equivalent to approximately -500 to -h450mV (SCE). Since the measured breakdown potentials of the present Ti-Ni alloys were higher than the highest corrosion potential found in the oral environment by as large as 700 mV, it seems that a breakdown of these alloys is very unlikely to occur in the oral environment.…”
Section: Materials and Methods 'mentioning
confidence: 99%
“…BERGMAN e/a/. (18,19) and NILNER (20) reported the maximum calculated current which two restorations in metallic contact can support under clinical conditions. The aim of the present study was to investigate a group of persons referred to the Faculty of Odontology, University of Umei regarding both general oral status and certain factors which could be related to corrosion in the oral cavity and to compare the results with those obtained from a control group.…”
mentioning
confidence: 99%
“…The total number of amalgam surfaces in the mouth was also registered in both groups. Finally potential and polarization measurements of existing and accessible dental metallic restorations were taken (15)..…”
Section: Materials and Metliodsmentioning
confidence: 99%